Metamaterial Based Sensor Using Fractal Hilbert Structure for Liquid Characterization - AbdulSattar, Rusul Khalid; Alibakhshikenari, Mohammad; Eiwi, Taha A.; Kouhalvandi, Lida; Hassains, Zaid A. Abdul; Virdee, Bal S.; Soruri, Mohammad; Tokan, Nurhan Turker; Parchin, Naser Ojaroudi; See, Chan Hwang; Livreri, Patrizia; Dayoub, Iyad; et al. (IEEE, 2023)
In this work, a simple and efficient approach is presented to design a metamaterial based sensitive sensor for liquid characterimtion. The proposed sensor based on the Hilbert structure has a compacted size of 40x60x1.6 mm(3). The Hilbert curve is used to enhance the sensitivity of the sensor by increasing the interaction area with the sample tested. The simulation studies are carried out by using the Computer Simulation Technology (CST) Microwave Studio. The resonant frequency of the proposed sensor is about 0.46 GHz. The resonant frequency has shifted approximately 30 MHz after the receptacle is printed on the sensor surface. The proposed sensor has successfully detected different samples of liquids. The variations of the resonant frequency, scattering parameters, bandwidth and quality factor of different samples are discussed.
Keywords: Metamaterial; Hilbert; fractal; receptacle; liquid characterization; Engineering